(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2020)
Nanocrystalline Fe3O4 and Fe2O3 particles were successfully synthesized by an innovative hybrid electrochemical-thermal method. The as-prepared compound was calcined for an hour from 100 to 600oC temperatures. The crystallinity, morphology and chemical state of the synthesized powders were characterized by XRD, TG-DTA, SEM/EDS, FT-IR, and UV–Vis spectral techniques after calcinations. The Brunauer–Emmett–Teller (BET) plots confirmed that iron oxide nanoparticles (NPs) calcined at 400oC has a surface area of 18.28 m2 g-1 with a total pore volume of 0.2064 cc g-1. From XRD pattern it is revealed that the precursor calcined at lower temperature (100-400oC) correspond to Fe3O4,while the ones calcined at higher temperature follow Fe2O3 pattern. The morphology of iron oxide NPs calcined at different temperatures were studied with scanning electron microscope (SEM) and exhibits spherical shaped geometries with average diameters of 80-150nm. Bangladesh J. Sci. Ind. Res.55(3), 221-228, 2020